Diagnosis and prognostic value of asymptomatic atrial fibrillation - U.P. Chernyaha-Royko; M.S. Sorokivskyy; A.V. Aker; O.J. Zharіnov (Кардіохірургія та інтервенційна кардіологія)
The aim of this publication was to summarize existing information on epidemiology, diagnosis and management of patients with silent atrial fibrillation (AF), as well as to present our studies concerning the frequency of silent AF in real clinical practice. Contemporary technologies of long-term electrocardiography monitoring often allow to detect silent AF in patients after stroke, transient ischemic attack or other thromboembolic events, after radiofrequency ablation or cardioversion in case of persistent AF, and to assess the «burden» of this arrhythmia. Our original prospective, single-center study included 150 patients with persistent AF or atrial flutter after cardioversion. Symptomatic recurrence of AF was detected by means of Holter ECG monitoring in 13.3 % of patients, asymptomatic AF – in 16 %. During the event-monitoring, 352 AF paroxysms were registered (278 episodes in 32 patients were symptomatic and 74 episodes in 18 patients were asymptomatic). In patients with silent AF the occurrence of thromboembolic events and heart failure with long-term observation is at least not less than in symptomatic patients. The detection of silent AF may influence the decision concerning antithrombotic treatment and assessment the appropriateness of heart rhythm control strategy.